Who makes the decision regarding the treatment of clinically localized prostate cancer–the patient or physician?. Issue 2 (11th July 2012) - Song, Lixin; Chen, Ronald C.; Bensen, Jeannette T.; Knafl, George J.; Nielsen, Matthew E.; Farnan, Laura; Wallen, Eric M.; Mishel, Merle; Pruthi, Raj S.; Mohler, James L.; Godley, Paul A.
Abstract BACKGROUND: The current study examined how patients' sociodemographic, cancer‐related, and subjective affective factors impacted their role in treatment decision‐making. METHODS: The patient sample (N = 788) was taken from a prospective follow‐up study of a population‐based cohort. Participants included 343 African American and 445 Caucasian‐American patients with clinically localized prostate cancer. Multinomial logistic regression was used to investigate relations between the explanatory variables and the nominal 3‐level decision‐making variable: patient‐only, patient‐physician shared, and physician‐only. RESULTS: Approximately 41% of patients reported patient‐only decision‐making, 45% reported shared decision‐making, and 13% reported physician‐only decision‐making. The odds of patient‐only over physician‐only decision‐making were greater for younger men (vs those aged ≥ 65 years) (odds ratio [OR], 1.68; 95% confidence interval [95% CI], 1.03‐2.74), and were less for men with high (vs low) cancer aggressiveness (OR, 0.29; 95% CI, 0.15‐0.55). The odds of shared over physician‐only decision‐making were less for men with high (vs low) cancer aggressiveness (OR, 0.40; 95% CI, 0.22‐0.73). Greater odds of patient‐only and shared decision‐making also were found to be associated with greater concerns about the physical impact of treatment and having enough time for decision‐making and lower scores of receiving advice from others. CONCLUSIONS: The findings of the current study indicate that, to facilitate a more patient‐oriented decision‐making process regarding treatment in those with clinically localized prostate cancer, clinicians need to tailor their interventions according to patient age and cancer aggressiveness, help reduce patient concerns and misconceptions regarding the physical impact of treatments, allow sufficient time for patients to consider treatment options, and assist patients in balancing advice and information received from different sources. Cancer 2013. © 2012 American Cancer Society.